University Students’ Reflection on Chosen Characteristics of National Populism in Slovakia - Sirotová, Mariana; Michvocíková, Veronika (Journal of Education Culture and Society, 2022)
Aim. The main aim of presented study is the exploration of university students´ reflection on chosen characteristics of national populism in Slovakia. Methods. For the main method of the study, a quantitative approach has been used. Students studying at universities in the Slovak Republic have been addressed via a questionnaire prepared in advance. Recorded answers of sixty-seven university students studying in the Slovak Republic have been analysed via first-degree data sorting. Results. The study has a theoretical-empirical character. In the theoretical part, there is a brief characteristic of national populism and characteristics of national-populistic tactics and strategies in Slovakia. In the empirical part, the analysis of surveyed university students´ opinions shows that most addressed university students studying at Slovak universities have not expressed a negative view of presenting the interests of the Slovak nation by political representatives. Conclusion. The addressed university students reflect on the issue of national populism on the Slovak political scene. On the other hand, respondents lack a relevant and expert view of the issue of national populism through the optics of a university educator who would (via his/her expert opinion) help students to identify undesired national-populistic tactics and strategies. A more detailed study of university students’ opinions related to their view of national populism and its manifestations in Slovakia should be supplemented by a qualitative study, using in-depth interviews.